2020
DOI: 10.1111/are.15050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the molluscicidal activity of the methanolic seed extracts ofZiziphus spina‐christiandCarica papayaon immunological and molecular aspects ofBiomphalaria alexandrinasnails

Abstract: Medicinal plants are still less expensive, safe to non‐target organisms, and eco‐friendly. The present work aims to evaluate the molluscicidal activity of the methanolic extract of Ziziphus spina‐christi and Carica papaya seeds against Biomphalaria alexandrina snails. The half lethal concentrations (LC50) of Z. spina‐christi and C. papaya were 108 and 138.5 mg/L, respectively after 24 h. LC10 of C. papaya created a pronounced induction in catalase (CAT) activity, while LC25 of Z. spina‐christi and LC50 of C. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The current work demonstrated that exposure of snails to the two algal extracts resulted in a change in the number of DNA bands as compared to control, and this indicated the genotoxic effect of the treatments. Ibrahim and Sayed (2021) also observed a difference in the DNA pattern of B . alexandrina snails treated with Carica papaya and Ziziphus spina ‐ christi seed extracts.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The current work demonstrated that exposure of snails to the two algal extracts resulted in a change in the number of DNA bands as compared to control, and this indicated the genotoxic effect of the treatments. Ibrahim and Sayed (2021) also observed a difference in the DNA pattern of B . alexandrina snails treated with Carica papaya and Ziziphus spina ‐ christi seed extracts.…”
Section: Discussionmentioning
confidence: 89%
“…Many researchers who have explored substances either from the biological or chemical origin as molluscicides have been interested in studying their effects on non‐target organisms (Ibrahim & Sayed, 2021; Saad et al, 2016; Santos et al, 2014; Silva & Pereira, 2019). This represents an important step to verify that the molluscicidal agent is environmentally friendly.…”
Section: Discussionmentioning
confidence: 99%
“…Schistosoma mansoni is a parasitic trematode species that inhabits several African and South American countries and is regarded as the species that causes schistosomiasis. The intermediate host of this parasite is a freshwater snail, Biomphalaria alexandrina (phylum Mollusca, class Gastropoda) [ 2 ]. Snails have risen to prominence in both the medical and economic fields as a result of their participation in the spread of diseases that afflict a wide variety of animals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis is a serious illness that has impacted the lives of people and animals around the world [ 1 ]. Schistosoma mansoni is a widely distributed parasitic species in many regions in Africa, the Middle East, and South America, where the intermediate host, a freshwater snail named Biomphalaria (phylum Mollusca, class Gastropoda), is located [ 2 ]. Snails have great medical, veterinary, and economic importance as they are the causative agent in transmitting diseases that affect many animals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%